Design and Construction of An Omnichannel Application at Dispendukcapil Surabaya - Fikko Muharavid Yoga Mardhany,; Utami, Ardhini Warih (Journal of Education Technology and Information System, 2025)
The customer service at Dispendukcapil Surabaya faces challenges in managing incoming messages from the public through various communication channels such as WhatsApp and Instagram. Unmonitored messages and a limited number of staff lead to delays in responding to complaints. Therefore, this study aims to develop an Omnichannel application that integrates WhatsApp and Instagram into a centralized platform, equipped with a keyword-based auto-reply feature to accelerate response time. The development method used is Rapid Application Development (RAD) with an iterative and fast-paced approach. Testing results show that the application successfully improves chat handling efficiency, accelerates response times, and provides a more integrated communication experience for the public. This study is expected to offer a solution to improve complaint and information service systems in government institutions.